Genre-Compositional and Lexical-Semantic Specifics of Advertising SEO-Texts - F. A. Nikolayev (Научный диалог, 2017)
Genre-compositional and lexical-semantic specifics of the English advertising SEO-texts, which are an integral part of advertising website, are considered. Advertising SEO-text is understood as a genre of advertising discourse in computer-mediated communication produced by taking into account the requirements of search engines and designed to produce a specific pragmatic effect - it urges the recipient to purchase or use the services. It is indicated that advertising SEO-text is not adequately considered in the scientific literature. It is shown that the appearance of this variety of the advertising text is determined by successful operation of the advertising sites in communicative space of the Internet, which in turn requires the use of specific technologies of text generation. The analysis is based on a corpus of advertising SEO-texts, selected by continuous sampling from the main pages of commercial sites in the UK and USA. Basic elements of genre and compositional structure of advertising SEO-text are identified, and their pragmatic and communicative functions are discussed. The analysis of means of implementation of text-forming categories of advertising SEO-text allowed the author to conclude that the category of cohesion is realized mainly by marking the main theme of SEO-text by lexical means of the language, which are in hypero-hyponymic and synonymic semantic relations and are the means of representation of underlying concepts designed to ensure the primary pragmatic function of advertising.